2017
DOI: 10.1021/jacs.7b07139
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Fluorescence Microscopy Reveals Local Diffusion Coefficients in the Pore Network of an Individual Catalyst Particle

Abstract: We used single-molecule fluorescence microscopy to study self-diffusion of a feedstock-like probe molecule with nanometer accuracy in the macropores of a micrometer-sized, real-life fluid catalytic cracking (FCC) particle. Movies of single fluorescent molecules allowed their movement through the pore network to be reconstructed. The observed tracks were classified into three different states by machine learning and all found to be distributed homogeneously over the particle. Most probe molecules (88%) were imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
110
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(119 citation statements)
references
References 24 publications
9
110
0
Order By: Relevance
“…5,6 At the forefront of verifying these models, and more importantly understanding transport at the micron scale, is the field of single particle tracking. [7][8][9][10] Here, we use singlemolecule conformational tracking (SMCT) to investigate the transport and conformational dynamics of linear and ring DNA molecules in biomimetic composite networks of actin and microtubules with varying types of crosslinking. Given the ubiquity of both linear and relaxed circular (ring) DNA in living organisms, and the implications that DNA transport in Traditionally, the impact of crowding on intracellular transport has been investigated using small globular proteins or synthetic polymers as the crowders, [30][31][32][33] which do not well model crowding by entangled and crosslinked networks of filaments that comprise the cytoskeleton.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 At the forefront of verifying these models, and more importantly understanding transport at the micron scale, is the field of single particle tracking. [7][8][9][10] Here, we use singlemolecule conformational tracking (SMCT) to investigate the transport and conformational dynamics of linear and ring DNA molecules in biomimetic composite networks of actin and microtubules with varying types of crosslinking. Given the ubiquity of both linear and relaxed circular (ring) DNA in living organisms, and the implications that DNA transport in Traditionally, the impact of crowding on intracellular transport has been investigated using small globular proteins or synthetic polymers as the crowders, [30][31][32][33] which do not well model crowding by entangled and crosslinked networks of filaments that comprise the cytoskeleton.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies based on the visualization methods such as interference microscopy (IFM) and infrared microscopy (IRM) discovered that, in addition to intracrystalline diffusion, surface barriers can also dominate the mass transfer of guest molecules in some nanoporous materials 3,12,16 . Recently, Weckhuysen et al 17,18 developed a fluorescence microscopy approach to directly observe the diffusion behavior in porous materials. It is shown that the diffusivity derived from the commonly used uptake/release rate measurement is in fact the apparent diffusivity reflecting the combined influence of intracrystalline diffusion and surface barriers in the nanoporous crystalline materials 6,15,19,20 .…”
mentioning
confidence: 99%
“…This has become a standard method for the analysis in zeolite catalysis. Weckhuysen and coworkers have developed a series of in situ methods for analyzing coke with in situ spectroscopy …”
Section: Traditional Methods Of Studying Diffusion and Deactivation Imentioning
confidence: 99%
“…Experimental results are complicated by that the diffusion coefficient is influenced by the zeolite structure, molecular structure, concentration, pore occupation, and the probable strong coupling of diffusion and deactivation . The measured average diffusion coefficient is actually a lumped parameter that cannot give detailed information.…”
Section: Traditional Methods Of Studying Diffusion and Deactivation Imentioning
confidence: 99%